Wali Nikah Anak Perempuan Yang Lahir dari Perempuan Hamil Luar Nikah Tinjauan Analisis Normatif dan Sosiologis (Studi di Kecamatan Sukakarya) - Herawati, Herawati (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2021)
This study aims to determine the normative law of marriage guardians for children born to pregnant women out of wedlock (this study focuses on the opinion of Imam Syafi'i) and to find out the views of the Sukakarya District community regarding guardianship of children born to pregnant women out of wedlock. This research is field research and library research. This study concludes that according to Imam Syafi'i the guardianship of a child resulting from adultery where there is no right for the biological father to marry off a child resulting from adultery the Prophet cancels the nasab relationship by way of adultery in Islam, does not recognize the nasab relationship with him after the arrival of Islam, then guardianship of the child out of wedlock the result of a pregnant woman out of wedlock if the child is going to marry then the guardianship falls on the guardian of the judge.